Poor Physical Function as a Risk Factor for Non-Communicable Diseases in Indonesia: A Retrospective Cohort Study - Risky Kusuma Hartono; Sabariah Abd Hamid; Muhammad Hafizurrachman (Interna Publishing, 2020)
Background: it cannot be ascertained whether an individual with poor physical function is at an increased risk of Non-Communicable Diseases (NCDs), thus the aim of this study is to examine this potential relationship. Methods: in this study, a fixed retrospective cohort design has been conducted by using data from the Indonesia Family Life Survey (IFLS) in 2007 and 2014. A total of 6,863 respondents who were not diagnosed with NCD by medical personnel in 2007 were successfully traced. After being controlled for covariates, the association between NCD type and poor physical function was measured by using the Adjusted Risk Ratio (ARR) and Population Attributable Risk (PAR). Results: respondents with poor physical function were at a significantly increased of being diagnosed with stroke (ARR: 6.9, 95%CI: 4.3-10.9), diabetes (ARR: 3.1, 95%CI: 2.4-4.1), or heart disease (ARR: 3.2, 95%CI: 2.4-4.5). The PAR score of respondents with diabetes was 0.006, meaning 0.6% of diabetes cases are attributed to poor physical function and can therefore be prevented if people maintain good physical function. Conclusion: poor physical function can be assessed to identify risk of diabetes, heart disease, and stroke. Healthcare personnel should provide education programs that inform patients on the importance of maintaining a healthy physical ability.